Enterotoxigenic Escherichia coli diarrhoea: acquired immunity and transmission in an endemic area - Black, Robert E. (1981)
Enterotoxigenic Escherichia coli (ETEC) are an important cause of diarrhoea in developing countries. Studies were made, in an endemic area of Bangladesh, of household contacts of patients with diarrhoea associated with E. coli producing heat-stable and heatlabile toxins (ST/LT) or heat-stable toxin (ST) only. It was found that 11% of contacts were infected in the 10-day study period, and that both the rate of infection and the proportion of infected persons with diarrhoea decreased with increasing age, suggesting the development of immunity. ETEC of the same serotype as that of the index patient were found in 9% of water sources used by index households, in a small number of food and drinking water specimens from the index homes, and in faeces from 3 healthy calves. The rate of infection of household members was highest in houses where there was contaminated food or water, which suggests that infection may take place in the home when contaminated water is brought in.